Use of reusable menstrual management materials and associated factors among women of reproductive age in Ghana: analysis of the 2017/18 Multiple Indicator Cluster Survey - Emmanuel Anongeba Anaba; Emilia Asuquo Udofia; Adom Manu; Anita Anima Daniels; Richmond Aryeetey (BMC, 2022)
Abstract Background The use of unsafe materials to collect menstrual blood predisposes women and girls to infections. There is a paucity of literature on the utilization of reusable menstrual materials in sub-Saharan Africa. This study examined factors associated with the use of reusable menstrual management materials among women of reproductive age in Ghana. Findings from this study can inform menstrual health programmes and reproductive health policy to address menstrual hygiene and specific areas of emphasis. Methods We analysed secondary data from the 2017/18 Ghana Multiple Indicator Cluster Survey. Descriptive statistics were employed to compute frequencies and percentages, while Chi-square and complex sample Binomial Logistic Regression was conducted to identify factors associated with the use of reusable menstrual materials. Results Half (52%) of the respondents were below 30 years old; mean (± sd) = 30.7(9.0). Thirteen percent used reusable materials to collect menstrual blood during their last period. Women aged 45-49 years (AOR = 5.34; 95% CI 3.47-8.19) were 5 times more likely to manage menstruation with reusable materials compared with those aged 15-19 years (p < 0.05). Women classified in the middle wealth quintile (AOR = 0.66; 95% CI 0.50-0.88) were 34% less likely to use reusable materials to collect menstrual blood compared with women in the poorest wealth quintile (p < 0.05). Also, women who were exposed to television (AOR = 0.78; 95% CI 0.61-0.99) had less odds of using reusable materials compared with women who were not exposed to television (p < 0.05). Conclusion This study showed that the use of reusable menstrual materials was influenced by socio-demographic factors, economic factors and exposure to mass media. Therefore, policies and programmes aimed at promoting menstrual health should focus on less privileged women. The mass media presents an opportunity for communicating menstrual hygiene.